Chemical Stability of a Chinese Herbal Spirit Using LC-MS-Based Metabolomics and Accelerated Tests - Hu, Yan; Wang, Zhe; Liu, Jiayue; Yang, Wen; Yang, Qiang; Liu, Yuan-Cai; You, Qiu-Yun; Chen, Xiao-Jia; Wan, Jian-Bo (Frontiers in Pharmacology, 2022)
As a prevalent medicinal liquor among Chinese people, a type of Chinese herbal spirit from Jing Brand Co., Ltd (CHS-J) is a newly developed health beverage with the health functions of anti-fatigue and immune enhancement. The researchers from the enterprise found that the contents of several components in CHS-J samples have been significantly decreasing during the stated storage period, as detected by the HPLC-UV method, which would make a great challenge for quality control of CHS-J. Furthermore, the chemical stability of CHS-J during the storage period is greatly challenged affected, especially in the environment of high temperature and light exposure. To systematically reveal the unstable components and promote the quality control of CHS-J, the chemical stability of CHS-J during the shelving storage period was characterized by the UPLC/Q-TOFMS-based metabolomics approach. First, the targeted and untargeted metabolomics approaches discovered the significantly changed components in CHS-J samples produced in different years. Furthermore, the accelerated tests of newly produced CHS samples and several authorized standards were conducted to validate the above results and elucidate the possible mechanisms underlying these chemical changes. Moreover, these chemical changes during the storage period had little influence on the anti-fatigue effect of CHS-J samples. These findings will offer new insight into the understanding of the chemical stability of CHS-J and will facilitate the quality control of CHS-J.